The nipple–areolar complex: comprehensive imaging review. Issue 3 (March 2021) - Lyons, D.; Wahab, R.A.; Vijapura, C.; Mahoney, M.C.
Abstract : The nipple–areolar complex can be affected by a variety of benign and malignant entities that can present with non-specific symptoms. Benign pathologies commonly affecting the nipple–areolar complex include nipple calcifications, nipple adenoma, abscess of Montgomery tubercles, ductal ectasia, periductal mastitis, and papilloma. Malignant pathologies that affect the nipple–areolar complex include Paget's disease of the breast, ductal carcinoma in-situ, and invasive ductal carcinoma. Clinical history and examination, imaging, and tissue sampling when appropriate are co-dependent factors that guide the assessment of nipple–areolar pathologies. This article provides a review of the normal anatomy, common anatomical variants, benign and malignant pathologies, and imaging techniques to guide the diagnostic assessment of the nipple–areolar complex.